Palynological Studies on Ten Species of Angiosperms from Nepal - Karna Mallick, Pushpa (International Journal of Applied Sciences and Biotechnology, 2017)
Palynological studies on ten species of angiosperms family namely Hibiscus rosa- sinensis L.(Malvaceae), Lilium candidum L. (Liliaceae), Petunia axillaris (Lam.) B.S.P.(Solanaceae) and seven species from family asteraceae namely Artemisia indica Willd., Aster ageratoides Kitam., Calendula offcinalis L., Cerpis japonica L. (Benth.), Sonchus asper (L.) Hill, Tagetus patula L., and Taraxicum officinale F.H.Wigg. was carried out. Result obtained from this investigation showed that pollen shape is spheroidal in Artemisia indica, Aster ageratoides, Calendula offcinalis, Hibiscus rosa- sinensis and P. axillaris; elliptical in L. candidum, hexagonal in S. asper and pentagonal in T. officinale; tricolpater in C.japonica. Pollen aperture is porate in all except in L.candidum where it is elliptic. Pollen wall is echinate in H.rosa-sinensis, A.ageratoides, T. patula; spinulate in P. axillaries, T. officinale, S. asper, C. japonica, C. officinalis and T. officinale and smooth in L. candidum. The general appearance of the pollen grain is circular in P. axillaries but longer than wide in L.candidum. The circular, echinate, large and triporate pollens seem to be primitive ones and spharoidal, hexaporate features have been regarded as comparatively advanced ones. Polyporate pollens are considered to be secondarily derived. The nature of the pollen grain in these species could be evolutionary significance. The similarities in structure of the pollen grain showed the inter- species relationships among the species and that’s why put in same family while the differences in structures showed reasons for them to exist as distinct species. Only one species namely L.candidum from monocot family (Liliaceae) included in this study. Int. J. Appl. Sci. Biotechnol. Vol 5(3): 361-365